Relationship of free - lingving nematode communities to some environmental characteristics in the organic shrimp farms, Ca Mau province - Tran, Thanh-Thai; Pham , Thanh-Luu; Nguyen , Tho; Ngo , Xuan-Quang (Vietnam Journal of Science and Technology, 2018)
Nematode communities (NC) in Tam Giang’s organic shrimp farms ponds (TGOSFP), Nam Can district, Ca Mau province were investigated in three seasons (March - dry, July - transfer and November - wet season) of 2015. Our findings underlined that the NC were expressed by high density and diversity. In addition, the environmental characteristics in TGOSFP may also be not quite optimal for shrimp farming because of high percentage of TN, TOC, low pH and anaerobic condition in sediment. The results of CCA analysis showed that main environmental parameters, such as TN, TOC, depth, DO, salinity and pH almost completely governed the abundances of several dominant gennera, things like Desmodora, Sabatieria, Terschellingia, Dichromadora, Pomponema, Halalaimus, Ptycholaimellus and Sphaerotheristus. Subsequently, the results of Pearson correlation confirmed that the abundances of genus Sabatieria, Terschellingia were significantly positive correlated with TOC, TN and depth. In contrast, genera like the Desmodora, Halalaimus and Ptycholaimellus had negative correlations with organic enrichment (TOC and TN). Additionally, almost genera were positively correlated with salinity. Analysis of the dominant nematode genera in combination with maturity index (MI) value are able to determine the ecological quality status of sediment (EcoQ) in TGOSFP. Results showed that moderate and poor EcoQ in most of TGOSFP throughtout the dry - trans - wet season. The attribute of NC and their correspondence with environmental characteristics can be considered as a good tool for environmental monitoring.